Balancing independence with accountability: A third-metre waltz?. Issue 1 (February 2019) - Petit, Christy Ann
This article assesses the past and current balance of independence with accountability for the European Central Bank (ECB). The concept of accountability is adapted to the central bank context, notably with the contextualisation of 'accountable independence' in the early ECB's inception. Different endogenous and exogenous determinants might influence such balance. If initially a communication-driven strategy embodied a somehow weak accountability regime, additional accountability practices – beyond the Treaty provisions – progressively readjusted the balance; yet, without guaranteeing to call and fully hold the ECB to account. The magnitude of the responsibilities assumed by the ECB in the recent years, after the economic and financial crisis, triggered an increased demand for accountability. The intensification of ECB's accountability practices, the provision of justifications beyond mere explanations and an increased scrutiny over the ECB all demonstrate an ongoing step towards an enhanced accountability regime. This is nevertheless a potentially reversible oscillation of the balance towards more accountability. The legal framework for ECB's accountability seems flexible enough to encompass accountable independence, independence but accountability, to a third-metre waltz of independence and accountability.